Perbedaan Ekspresi CD56 pada Hiperplasia Nodular, Adenoma Folikular dan Karsinoma Papiler Tiroid - Apitriani; Amalia Octaviani Dewi; Mezfi Unita (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
BackgroundThyroid carcinomas are the most common malignancy of endocrine organs and the fourth most common cancer of women inIndonesia. Most of these tumors derived from thyroid follicular cells and more than 85% of cases are papillary carcinoma. Somecases may be confusing and cause misdiagnosis due to the morphology of these tumors are frequent overlap between nodularhyperplasia, follicular adenoma and papillary carcinoma. Anti-CD56 is one of the diagnostic markers with high sensitivity andspecificity in distinguishing benign thyroid lesions and papillary carcinoma. The aims of this study is to analyze the differences ofCD56 expression in nodular hyperplasia, follicular adenoma and papillary carcinoma.MethodsAn observational study with cross-sectional design was performed at Departement of Anatomical Pathology Faculty of MedicineUniversity of Sriwijaya/Dr. Mohammad Hoesin Palembang, from 1st January 2014 to 30th June 2017. Paraffin blocks of 52 samplesare collected from nodular hyperplasia (24 cases), follicular adenoma (8 cases) and papillary carcinoma (20 cases). The slides wereimmune stained using CD56 antibody. The difference of CD56 expression between papillary carcinoma and nodular hyperplasiawas analyzed using Chi-Square test while those between papillary carcinoma among follicular adenoma was analyzed usingFisher’s exact test.ResultsIn all samples of papillary carcinoma CD56 expression was negative compared to totally positive reaction in all samples of nodularhyperplasia and follicular adenoma.ConclusionAnti-CD56 could be used as a diagnostic marker in distinguishing between papillary carcinoma, nodular hyperplasia and follicularadenoma.